Implementasi Perpres Nomor 118 Tahun 2022 Tentang Rencana Induk Pengelolaan Batas Wilayah Negara dan Kawasan Perbatasan Tahun 2020-2024 Terhadap Pulau Sebatik - Mariano Hermando Boymau; Novita Scolatika Totnay; Yonanes Arman (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Indonesia is the largest archipelagic country in the world which is very strategically located, both economically and geopolitically. The archipelago in Indonesia is united by a vast ocean and some of them are directly adjacent to several neighboring countries, both land and sea. In conducting a researcher refers to research methods, so that research is more directed and planned. The research method that the author uses is a normative juridical research method This research uses a statutory approach (Statute-Approach) related to what the researcher wants to research. Perpes No.31 of 2015 was issued to implement the provisions of article 21 paragraph (1) of Law Number 26 of 2007 concerning Spatial Planning and Article 123 Paragraph (4) of Government Regulation Number 26 of 2008 concerning Spatial Planning of State Border Areas in Kalimantan, which in the policy states that the Spatial Plan of Islands and National Strategic Areas is regulated by Perpes. Sebatik Island is the outermost small island owned by two countries, namely Indonesia and Malaysia, so the threat to the security and sovereignty of the country on the island is quite vulnerable, therefore, it is very important to overcome problems that can threaten the security and sovereignty of the country on this island.